THE EFFECT OF EVENT ACTIVATION ON BRAND AWARENESS AND ITS IMPLICATIONS ON PURCHASE INTENTION OF PROMAG HERBAL PRODUCTS IN BANDUNG - Gia Ginanjar; Nur Hayati (RADJA PUBLIKA, 2026)
Indonesia's herbal pharmaceutical industry faces challenges in increasing brand awareness and purchase intention through effective event activation strategies. This study analyzes the effect of event activation on brand awareness and its implications for purchase intention of Promag Herbal products at PT. Kalbe Farma Bandung Branch, with brand awareness as a mediating variable. Internal data paradox shows event activation intensity reaches 126.88% of target, yet event sales only achieve 71.32% of event sales target. The study uses quantitative descriptive-verification approach with 110 respondents and SEM-PLS analysis. Test results show: (1) event activation has positive significant effect on brand awareness (β = 0.694; T = 11.016; p < 0.001); (2) brand awareness has a positive significant effect on purchase intention (β = 0.648; T = 8.202; p < 0.001); and (3) brand awareness partially mediates the effect of event activation on purchase intention (VAF = 68.9%). These findings confirm that the quality of event activation is more important than quantity in forming strong brand awareness as transmission mechanism toward consumer purchase intention.